2013
DOI: 10.1117/12.981979
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the interaction of alkali ions with surfactant head groups for the formation of lyotropic biaxial nematic phase via optical birefringence measurements

Abstract: Lyotropic liquid crystals exhibiting nematic phases were obtained from the mixtures potassium laurate/alkali sulfate salts (M 2 SO 4 )/1-undecanol (UndeOH)/water and sodium dodecyl sulfate (SDS)/M 2 SO 4 /1-dodecanol (DDeOH)/water, where M 2 SO 4 represents the alkali sulfate salts being Li 2 SO 4 , Na 2 SO 4 , K 2 SO 4 , Rb 2 SO 4 or Cs 2 SO 4 . The birefringences measurements were performed via laser conoscopy. Our results indicated that cosmotropic and chaotropic behaviors of both ions and head groups are v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Recent studies have shown that the choice of components of lyotropic mixtures is a key issue for the stabilisation of both uniaxial and biaxial nematic phases [10,11] and also cholesteric [12] phases. For instance, alcohols having long and straight alkyl chain were used as co-surfactants, and their alkyl chain lengths, n a , play an important role on the preparation of mixtures that give the nematic phases.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that the choice of components of lyotropic mixtures is a key issue for the stabilisation of both uniaxial and biaxial nematic phases [10,11] and also cholesteric [12] phases. For instance, alcohols having long and straight alkyl chain were used as co-surfactants, and their alkyl chain lengths, n a , play an important role on the preparation of mixtures that give the nematic phases.…”
Section: Introductionmentioning
confidence: 99%
“…The alkali salts (sodium salts) were Li2SO4, Na2SO4, K2SO4, Rb2SO4 and Cs2SO4 (Na2SO4, NaF, NaCl, NaBr, NaNO3, NaClO4 and NaSCN). The results [14] indicated that when the surfactant head groups and the ions bound to them at the micelle's surface exhibit the same property in terms of the chaotropic or kosmotropic The results discussed in [88] may be considered as preliminary. For this reason, complementary investigations were needed to understand the effect of the specific interactions between the ionic species at the micelle surfaces on the stabilization of the lyotropic nematic phases, especially the biaxial.…”
Section: Effect Of Interactions Between Head Groups and Ions Of Electmentioning
confidence: 90%
“…Consequently, it would be better to conclude that the larger value of the birefringences is attributed to the formation of tightly bound ion-pairs at the micelle surfaces. The results discussed in [88] may be considered as preliminary. For this reason, complementary investigations were needed to understand the effect of the specific interactions between the ionic species at the micelle surfaces on the stabilization of the lyotropic nematic phases, especially the biaxial.…”
Section: Effect Of Interactions Between Head Groups and Ions Of Electmentioning
confidence: 96%
See 2 more Smart Citations